Situation in grammar or in frames? : Evidence from the so-called baby talk register - Fischer, Kerstin (Constructions and Frames, 2015)
This paper addresses the conditions under which knowledge of situation-specific language use should be part of a construction grammatical representation and under which it should, rather, be part of a frame semantic representation. Using child-directed speech as an example, which has been suggested to constitute a good candidate for a register, it is shown that a conventional association between grammatical form and situation is implausible. Instead, the relationship between grammar and situation is mediated by speakers’ understandings of the functional affordances of the respective situation, to which the communication partner may contribute considerably. In the case of the so-called baby talk register, situational knowledge is thus stored best in semantic frames as a set of functions that can be demonstrated to be commonly attended to, whereas construction grammar remains an inventory of general form-function pairs.
https://katalog.adlr.link/Record/ai-49-aHR0cDovL2R4LmRvaS5vcmcvMTAuMTA3NS9jZi43LjIuMDRmaXM